Chapter Leonardo negli studi ottocenteschi sulla cartografia delle Alpi - GIANASSO, ELENA (Territori, 2023)
Leonardo's manuscripts contain many quotes of 'his' Western Alps, well-known mountains sketched, with lakes, rivers and towns, creating outstanding territorial readings. In the 19th century, he became a turning point between medieval representation techniques and the great cartographic reform of the 16th century. Leonardo's approach to territorial drawing, his evolutionary theories on the history of the Earth, his measuring and survey instruments, his calculation of mountains altitudes can be compared to subsequent maps confirming, , with ideal overlaps, the crystal clear anticipations of the 'Grande di Vinci'.